2021
DOI: 10.1111/ppl.13330
|View full text |Cite
|
Sign up to set email alerts
|

The HD‐Zip I transcription factor MdHB7‐like confers tolerance to salinity in transgenic apple (Malus domestica)

Abstract: Salinity is a major environmental constraint that substantially limits global agricultural productivity. HD-Zip I transcription factors are involved in plant responses to salt stress, but little is known about the HD-Zip I genes in apple (Malus domestica). Here, we characterized the function of an apple HD-Zip I gene (MdHB7-like) and report that its expression is induced by salt stress. To further explore its role in salt stress, we created MdHB7-like overexpressing and RNAi transgenic apple plants. The overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…To explore the mechanism underlying salt‐induced MdATG18a expression and autophagic activity, the MdATG18a promoter sequence was cloned and used to screen the apple cDNA library using the Y1H assays. The screening results revealed that MdHB7‐like, an HD‐Zip I protein that positively regulates apple salt tolerance (Zhao et al., 2021), is bound to the MdATG18a promoter in yeast (Figure 6a). Electrophoretic mobility shift assays (EMSAs) were performed to further verify the direct binding of MdHB7‐like to the MdATG18a promoter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the mechanism underlying salt‐induced MdATG18a expression and autophagic activity, the MdATG18a promoter sequence was cloned and used to screen the apple cDNA library using the Y1H assays. The screening results revealed that MdHB7‐like, an HD‐Zip I protein that positively regulates apple salt tolerance (Zhao et al., 2021), is bound to the MdATG18a promoter in yeast (Figure 6a). Electrophoretic mobility shift assays (EMSAs) were performed to further verify the direct binding of MdHB7‐like to the MdATG18a promoter.…”
Section: Resultsmentioning
confidence: 99%
“…However, our knowledge of the mechanism of salt stress‐induced autophagy, particularly in perennial woody plants, is limited. Our previous studies have shown that the HD‐Zip I TFs play positive roles in the response to salt stress in apples (Zhao, Gao, Jia, Li, et al., 2021; Zhao et al., 2021), but the regulatory mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these homeodomain leucine zipper class I (HD-Zip I) possessed the properties of hubs and bottlenecks in our analyses, indicating the importance of these two key players in ADGCN ( Table S1 ). Remarkably, apple plants overexpressing HB-7 were more tolerant to drought treatment, maintained a high rate of photosynthesis, and accumulated increased biomass, suggesting the potential use of our network science-based discovery in genome editing and engineering programs for economically important plant species [ 70 , 71 ]. It is also important to point out that, while the current study examined the importance of transcriptome in discovering novel players in drought, this abiotic stress is manifested by intricate synergistic and antagonistic signals that cannot be fully captured by RNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have also confirmed that 14-3-3 proteins can regulate the expression of antioxidant enzyme gene in response to stresses ( Manosalva et al., 2011 ; Li et al., 2014 ). In apple, many genes such as MdMYB46 , MdWRKY30 , and MdHB - 7 are important components of the gene network that is involved in the regulation of reactive oxygen species-related genes, and they regulate ROS scavenging in response to salt stress ( Chen K. et al., 2019 ; Dong et al., 2020 ; Zhao et al., 2021 ). Here, we found that the expression of MdMYB46 , MdWRKY30 , and MdHB-7 was decreased in MdGRF6-OE plants, and increased in MdGRF6-RNAi plants ( Figures 8F–H ).…”
Section: Discussionmentioning
confidence: 99%